Konsep Self-actualized Abraham Maslow: Perspektif Psikologi Sufistik - Annajih, Moh. Ziyadul Haq; Sa'idah, Ishlakhatus; Taufik (Universitas Islam Negeri Madura, 2023)
Self-actualization is the peak experience in Maslow's hierarchy of needs theory. Maslow's hierarchy of needs consists of physiological needs, the need for a sense of security (safety needs), the need to have affection (social needs), esteem needs, and self-actualization. The purpose of this study is to describe how Maslow's holistic-dynamic theory describes self-actualization and the Sufistic view of the concept of self-actualization. This study employs a qualitative research method in conjunction with a type of literature review. The data collection technique used is documentation. The results of the study show that Sufistic psychology views self-actualization as a peak experience that is not absolute because humans are not just physical, mechanical beings. Ibn 'Arabi views that humans will reach a peak experience when they have abandoned themselves to unite with God (fana'); then humans must experience four levels: Shari'a, Tariqah, essence, and makrifat. In addition, al-Ghazali also emphasized the fulfillment of mashlahah al-'amm as his peak experience.